Разрушение сварных алюминиевых труб - Миллер, К.Дж. (Автоматическая сварка, 2003)
Приведены результаты исследований причин разрушения труб из алюминиевого сплава 6061-Т6, полученных прессованием. Использованы всесторонние подходы, учитывающие особенности процесса производства, трехмерный анализ напряжений, механику разрушения, микроструктуру и другие. Даны рекомендации по предупреждению разрушений. A failure investigation concerning 6061-T6 aluminium tubes as produced by an extrusion process, required an extensive and detailed study. This involved ten aspects, namely the manufacturing process; 3D finite element stress analysis; microstructural fracture mechanics; metallurgical considerations; international codes and specifications; residual stresses; Raman spectra analyses; environmental factors an extremely long-life fatigue failure assessment; and recommendations as to how to avoid future failures. Obviously the investigation required a multi- and inter-disciplinary approach. At the start of the study the opinions of several experts were sought. At the termination of the investigation successful recommendations were made to the manufacturers that avoided future failures. The brief case history presented in this paper is a useful exercise for students of microstructural fracture mechanics and fatigue failure analyses.